An Islamic Religious Education-Based Manners Program in Phase C Public Elementary Schools - Muhammad Ma'sum; Akhmad Alim; Nesia Andriana; Stefan Th. Gries (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Many students still have problems with manners and etiquette, both in their attitudes and behaviour in everyday life. The study aims to develop a manners habit formation programme based on Islamic education at Fase C Public Primary School. The study uses the ADDIE research and development (R&D) approach. The research subjects were teachers, Phase C students, and parents of students. The research findings indicate that the Islamic education-based manners training programme at Phase C Public Elementary School is feasible and practical. The implementation of the manners training programme has a positive impact on improving students' manners.